2021
DOI: 10.1038/s41377-021-00491-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh numerical aperture meta-fibre for flexible optical trapping

Abstract: Strong focusing on diffraction-limited spots is essential for many photonic applications and is particularly relevant for optical trapping; however, all currently used approaches fail to simultaneously provide flexible transportation of light, straightforward implementation, compatibility with waveguide circuitry, and strong focusing. Here, we demonstrate the design and 3D nanoprinting of an ultrahigh numerical aperture meta-fibre for highly flexible optical trapping. Taking into account the peculiarities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 55 publications
(78 reference statements)
1
75
0
Order By: Relevance
“…All in all, we anticipate that the non-diffracting beam will continue to contribute to many of the biomedical application researches to overcome the light scattering and large penetration drawbacks. With the recent advances in metasurface design [164] and fabrication of optical fiber, it is possible to integrate the non-diffracting beam with optical fiber for easy delivery of the non-diffracting beam [165]. With the non-paraxial beams, it would be possible to further improve the axial resolution of the MABs in the volumetric two-photon imaging system [17,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…All in all, we anticipate that the non-diffracting beam will continue to contribute to many of the biomedical application researches to overcome the light scattering and large penetration drawbacks. With the recent advances in metasurface design [164] and fabrication of optical fiber, it is possible to integrate the non-diffracting beam with optical fiber for easy delivery of the non-diffracting beam [165]. With the non-paraxial beams, it would be possible to further improve the axial resolution of the MABs in the volumetric two-photon imaging system [17,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the ultrathin, compact, and flat design of metasurfaces, multiple optical trapping potentials can be realized for parallel guiding and sorting of particles [20,52]. Moreover, our metasurface based on beam shaper can be directly integrated with fiber optic probes and microfluidic devices [60,62]. Moreover, a tunable metasurface based on beam shaper can be designed to adjust trapping potentials along the axial direction [63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Such a combination has been addressed by Yang et al, [22] who demonstrated the realization of a plasmonic metalens on the core of a sophisticated microstructured fiber via focused ion-beam milling (i.e., large-core photonic crystal fibers) operating at a near-infrared wavelength. One application that particularly benefits from the implementation of MSs on fiber end faces, for example, is the remote optical trapping of microscopic particles, which has recently been reported by Plidschun et al, [23] who demonstrated the implementation of a high-numerical-aperture MS (numerical aperture [NA] > 0.88) on the tip of a commercial single-mode fiber for trapping individual bacteria within an aqueous environment.…”
Section: Doi: 101002/adpr202100100mentioning
confidence: 99%